Thrown in at the deep end? Perceptions of burdens, gains, and contributions to the integration of refugee students among teachers with(out) target group-specific professional knowledge - Spanner, Franziska; Maué, Elisabeth (Frontiers in Sociology, 2022)
In Germany, young migrants and refugees whose German language skills are not sufficient for attending regular classes at school are assigned to so-called “preparation classes”. As the name implies, the main objective of these classes is to teach German language skills and thereby prepare students for regular classes or vocational education and training. Teachers in these classes face special challenges: They have to teach a group of students that is highly heterogeneous in several key respects, they have to deal with a dearth of institutional support and guidance, and they have a lot of responsibility regarding their students' integration in Germany. Therefore, this paper asks what target group-specific professional knowledge teachers possess and to what extent this knowledge reduces the teachers' burdens and raises their perception of gains and contributions to their students' success. Our mixed-method survey of 48 teachers of refugees in prevocational preparation classes in Germany shows that the majority of teachers acquired useful knowledge for teaching refugees, e.g., dealing with trauma and post-traumatic stress disorder, building German proficiency, or language-sensitive teaching, by attending professional training. In sum, most of the teachers saw immigration to Germany as both a problem and an opportunity. The main burdens they identify are bad working conditions, a lack of support and appreciation and a high demand for high flexibility. Despite generally low stress levels and high resilience, the teachers were extremely stressed by the heterogeneity in their students' performance, especially those teachers who had completed professional training. However, teachers appreciated the students' willingness to learn and gratitude, and perceived cultural diversity in the classroom as a gain for themselves and their teaching. The teachers felt they had mostly contributed to their students' acquisition of the German language as well as their educational progress in general and their personal development. Students' chances of success are expected to be especially high in the German language acquisition and the management of everyday life in Germany. The assessments of teachers with and without target group-specific professional knowledge differ only slightly and rarely significantly.